Epigallocatechin Gallate Can Protect Mice From Acute Stress Induced by LPS While Stabilizing Gut Microbes and Serum Metabolites Levels - Ma, Yong; Liu, Gang; Tang, Muyang; Fang, Jun; Jiang, Hongmei (Frontiers in Immunology, 2021)
Epigallocatechin gallate has potent biological activity, a strong antioxidant, and anti-inflammatory effects. This study aims to explore the mitigation effect of EGCG on LPS-induced acute injury. We randomly divided 18 mice into three groups: CON, LPS, and LPS-EGCG. We gave LPS-EGCG gavage treatment with EGCG on day 8-15 and intraperitoneal injection of LPS on day 16 to induce acute injury. The results showed that compared with the LPS group, the bodyweight of the mice in the LPS-EGCG group increased significantly, and the morphological damage of the jejunum and liver was effectively alleviated. We measured liver tissue and found that EGCG gavage treatment significantly reduced the pro-inflammatory factors (TNF-α, IL-1β, IL-6, MCP-1, MIP-2, IFN-γ) and oxidation indicators (MPO, NO, ALT, and AST) induced by LPS content. The microbiological results showed that EGCG gavage treatment reshaped the disturbance of the intestinal microbial community in mice caused by LPS, reversed the changes in the abundance ratio of Firmicutes/Bacteroidetes, and significantly reduced the abundance of Enterobacteriales. Finally, the results of serum metabolomics showed that compare with the LPS group, the gavage treatment of EGCG significantly increased the content of sphingomyelin (d17:1/17:0), sphingomyelin (d16:1/20:0), and so on and significantly reduced the content of trans-Hexadec-2-enoyl carnitine, and so on. Therefore, we believe that EGCG can alleviate the acute injury induced by LPS by remodeling the microbial structure of the intestines, improving the metabolism of sphingolipids, and inhibiting the content of harmful